Inpatient care of sick newborns in special new born care units in Odisha - Sahu, Dayasis; Godara, Naresh R. (International Journal of Contemporary Pediatrics, 2025)
Background: Inpatient care assessment of sick newborns in Special New Born Care Units (SNCUs) in Odisha is vital for feedback and improvement. This study aimed to characterize the quality of care provided by SNCUs in selected districts in Odisha during 2020-2022. Methods: Using secondary data from 10 SNCUs of District Hospitals in Odisha over a three-year period (2020–2022), we performed a cross-sectional descriptive analysis on all admitted neonates. Age, gender, birth weight, admission indication, maturity, mortality profile, referral, and admission pattern were all profiled. Excel 2021 was used to extract the data, and Excel and Epi Info were used for analysis. Results: Of the 50226 babies admitted to SNCUs, 24383 (48.5%) were inborn. Males made- up 58.4% of the infants. 995 babies (2.0%) weighed less than 1000 grams, while 58.5% of neonates had low birth weights (less than 2500 grams). Prematurity (n=4363, 8.7%), low birth weight (n=6757, 13.5%), refusal to feed (n=5327, 10.6%), neonatal jaundice (n=9616, 19.1%), and perinatal asphyxia (n=14421) account for 28.7% of hospitalizations. Of the total, 4.1% left the SNCU against medical advice, 9.7% died, 11.3% were referred, and 74.8% were discharged. The leading causes of death were preterm birth, infection, hypoxic-ischemic-encephalopathy (HIE), and birth asphyxia. The Composite SQCI performs satisfactorily (0.60-0.66) over the course of the twelve quarters Conclusion: Birth asphyxia is the primary cause of illness and mortality in neonates. Early referrals, effective intervention, and excellent prenatal care are essential to prevent it.